TEV-48125 for the preventive treatment of chronic migraine: Efficacy at early time points. (5th July 2016) - Bigal, Marcelo E.; Dodick, David W.; Krymchantowski, Abouch V.; VanderPluym, Juliana H.; Tepper, Stewart J.; Aycardi, Ernesto; Loupe, Pippa S.; Ma, Yuju; Goadsby, Peter J.
Abstract : Objective: To evaluate the onset of efficacy of TEV-48125, a monoclonal antibody against calcitonin gene-related peptide, recently shown to be effective for the preventive treatment of chronic migraine (CM) and high-frequency episodic migraine. Methods: A randomized placebo-controlled study tested once-monthly injections of TEV-48125 675/225 mg or 900 mg vs placebo. Headache information was captured daily using an electronic headache diary. The primary endpoint was change from baseline in the number of headache hours in month 3. Herein, we assess the efficacy of each dose at earlier time points. Results: The sample consisted of 261 patients. For headache hours, the 675/225-mg dose separated from placebo on day 7 and the 900-mg dose separated from placebo after 3 days of therapy ( p = 0.048 and p = 0.033, respectively). For both the 675/225-mg and 900-mg doses, the improvement was sustained through the second ( p = 0.004 and p < 0.001) and third ( p = 0.025 and p < 0.001) weeks of therapy and throughout the study (month 3, p = 0.0386 and p = 0.0057). For change in weekly headache days of at least moderate intensity, both doses were superior to placebo at week 2 ( p = 0.031 and p = 0.005). Conclusions: TEV-48125 demonstrated a significant improvement within 1 week of therapy initiation in patients with CM. Classification of evidence: This study provides Class II evidence that for patients with CM, TEV-48125 significantly decreases the number of headache hours within 3 to 7 days of injection.